2018
DOI: 10.1080/07448481.2018.1484366
|View full text |Cite
|
Sign up to set email alerts
|

(Unintended) Consequences of initiating an alcohol sales policy at college football stadiums: A case study

Abstract: University officials are increasingly considering selling alcoholic beverages at campus football stadiums. To inform this decision, we report on offenses occurring at a campus football stadium and surrounding community on game day weekends between 2009 and 2013. Campus police log data for 35 home football weekends were examined, accounting for 1,940 distinct incidents. There was a general upward trend in crime incidents. On average, 330 total crime incidents occurred when alcohol was not sold (2009-2011) compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…While there was an abundance of EMS calls and ED visits within the dates studied, it will be important to analyze longitudinal trends, as was done over a three-year period in Barry’s 2019 study. 11 Another limitation of our study is the effect of the COVID-19 pandemic. While 2020 was excluded due to the effects of the pandemic, it is possible that the 2021 data was also affected by the personal and institutional responses to the pandemic.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…While there was an abundance of EMS calls and ED visits within the dates studied, it will be important to analyze longitudinal trends, as was done over a three-year period in Barry’s 2019 study. 11 Another limitation of our study is the effect of the COVID-19 pandemic. While 2020 was excluded due to the effects of the pandemic, it is possible that the 2021 data was also affected by the personal and institutional responses to the pandemic.…”
Section: Limitationsmentioning
confidence: 96%
“…9,10 Researchers at a large Midwestern university found a linear increase in alcohol-related incidents in the three years after the implementation of stadium alcohol sales. 11 An analysis of police campus records from 12 Division 1 football universities found that criminal incidents were significantly more common on game days than non-game days, but that there was no significant increase in incidents following the introduction of in-stadium sales. 6 Although the health impact of alcohol sales is unclear, the financial benefit to the university is more predictable.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the impact of alcohol sales adoption, Barry et al (2019) find that criminal incidents increased for an FBS school (identity of school not disclosed) in the two years after alcohol sales were instituted, relative to the level of incidents in the three years preceding the policy change. Similarly, using an expanded sample of seven FBS schools, some of which sell alcohol on game days, Menaker and Chaney (2014) find some evidence that alcohol sales are positively correlated with alcohol-related arrests, although the strongest positive correlation is found for attendance and crime.…”
Section: Alcohol Sales At College Football Games and Crimementioning
confidence: 99%
“…However, it is theoretically ambiguous whether game day alcohol sales contribute to increased alcohol consumption and intoxication. Until very recently, little was known empirically about the crime-related consequences of stadium alcohol policies, apart from a handful of case studies (Barry et al, 2019; Bormann & Stone, 2001; Boyes & Faith, 1993; Menaker & Chaney, 2014). In a working paper, Blemings (2020) finds that the introduction of alcohol sales at FBS college football games is associated with reductions in crime for 21-to-23 year-olds (compared to 18-to-20 year-olds) on home game days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation